Análise da performance de aerogeradores verticais H utilizando o modelo de múltiplos tubos de corrente e dinâmica dos fluidos computacional - Pontes, Larissa da Silva (2021)
The present work analyzes the performance of an H-type Darrieus wind turbine through a method based on the concepts of blade element and momentum (BEM – Blade Element Momentum), known as the multiple streamtube method (implemented by SANDIA/USA laboratories as code DART-DARrieus Turbine) and through Computational Fluid Dynamics (CFD - Computational Fluid Dynamics) via Fluent/ANSYS software. The main objective is to compare the results obtained by the two methods for a simplified two-dimensional geometry of a scaled H rotor, whose dimensions were obtained through a process of optimization of wind rotors on the DART code for maximum wind energy extraction based on the wind data collected at the meteorological station OMM:08798 (Latitude: -7.1°; Longitude: -34.86°) located at the Solar Energy Laboratory (LES/UFPB), João Pessoa, Brazil. The wind data represent a historical series of the last 40 years measured at 7.43 meters high and which have been extrapolated to a height of 100 m. Although slightly different, the results show that the DART code (Cpmax = 0.29, λmax = 3.4) can be used as a good initial approximation for H-type vertical wind rotor designs, which should be further analyzed in greater detail through more sophisticated methods as Computational Fluid Dynamics (Cpmax = 0.24, λmax = 3.0), since important phenomena such as mat effects on the blades in the posterior region of the rotor center, dynamic stall, curvature effects of the flow and presence of the axis, are not captured by the simplified model.